Open-air museums: prospects for innovative development - Lysіuk, Tatiana V. (My University, 2023)
The article examines Ukrainian skansens as open-air museums of architecture and ethnography that reflect the centuries-old experience of the historical development of the Ukrainian people and represent their spiritual culture. It is determined that skansen museums are an innovative type of museums aimed at reproducing traditional forms of folk life in various fields. The nature of the exposition and the size of the skansen's territory make it possible to have a spectacular element – folk gatherings, celebrations, festivals. That is why such museums are the keepers of national traditions, active participants in tourist and entertainment activities aimed at popularising folk culture and a centre of spiritual revival of the deep traditions of the Ukrainian people. The article reveals the uniqueness of Ukrainian skansen museums as a tourist and recreational resource base that enhances the attractiveness of national cultural, historical and architectural sites, contributes to aesthetic pleasure, informational and emotional saturation of visitors and, of course, comfortable recreational conditions..
Keywords: museum; Ukrainian; open-air museums; skansen museums